A apreensão de correio eletrónico no processo penal português - Cavaco, Joana Filipa Martins (2022)
Electronic mail messages are an indespensable means of evidence for the investigation of certain crimes. Therefore, it is essencial to clearly and rigorously explain its the current legal framework, pointing out its main issues. The Seizure of electronic mail messages is regulated under article 17th of the Cybercrime Law, which, while establishing some of the requirements and preassumptions, does refer to the correspondence seizure regime envisaged by the Criminal Procedure Code. The technical and legal dissimilarities of electronic mail, when compared to traditional correspondence, originate inconsistencies in the system that end up leading to the wrongful attribution of different constitutional protection, in totally contradictory jurisprudential decisions and in violation or derogation of the norm, deprived of any legal basis. The main focus of the present study is the defense of an interpretation which has both as a starting and arrival point, on the one side, the constitutional principles, and, on the other, the written law, that allows for a clear and uniform application of the norm, keeping a minimum of verbal congruity with what it establishes, and, mainly, a greater legal predictability and security. Multiple theses may be derived from the present study. Those will, after all, correspond to the answers for the controversial questions tal will, hereby, be analysed. It can be, henceforth, advanced that one of the main theses reached is that electronic mail messages, regardless of its status, requires the same constitutional tutelage which is granted to communications, but, given its specificities, lacks a particular and autonomous regime, adapted to the requests introduced by digital evidence in the current portuguese criminal procedure system.